February 6, 1934: The Veterans' Riot - Chris Millington (French Historical Studies, 2010)
On February 6, 1934, nationalist leagues and Great War veterans rioted in Paris. The next day the elected radical government resigned, despite having won three votes of confidence. A conservative government took its place. Street violence had restored the right to power. Histories of the riot have generally contrasted the violence of the paramilitary leagues with the peaceful march of the Union Nationale des Combattants (UNC). Veterans' associations are largely understood to have been republican and an obstacle to the development of fascism France. This article challenges this historiography. In examining the violence of veterans and their interpretation of the riot, the article shows that a straightforward understanding of the veterans as republican is untenable. Veterans throughout the UNC were gladdened to see the government fall and hoped that a more authoritarian regime would soon be installed.